Extract of Rhus verniciflua Stokes enhances Th1 response and NK cell activity - Lee, Eui-joon; Lee, Gihyun; Sohn, Sung-Hwa; Bae, Hyunsu (Molecular & cellular toxicology, 2016)
Rhus verniciflua Stokes (RVS) is a common poison ivy that causes allergic dermatitis. However, it has been used in Korean Medicine as a therapeutic herb, traditionally for the treatment of abdominal masses. Recent studies have demonstrated evidence of anti-tumoral effects by RVS. However, the effect of RVS on tumor-targeting immune cells such as NK cells and helper T cells remains to be verified. The purposes of this study are as follows: (1) determine whether RVS increases NK cell activity and (2) determine whether RVS increases the expression of cytokines, such as IFN-γ, TNF-α, IL-4, IL-5, and IL-10, from Th1 and Th2 cells. NK cells and CD4 T-cells from the spleens of BALB/c mice were highly purified using magnetic beads. CD4 T-cells were polarized to Th1-cells by rIL-12 and anti-IL-4 antibody or to Th2-cells by rIL-4 and anti-IL-12 antibody. RVS directly increased NK cell activity in a calcein-AM release assay and augmented IFN-γ and TNF-α secretion from Th1-cells in an ELISA assay. Thus, these results suggest that RVS may stimulate therapeutic immune responses against cancer via NK cells and Th1 cells.